Low-Frequency versus High-Frequency Ultrasound-Mediated Transdermal Delivery of Agomelatine-Loaded Invasomes: Development, Optimization and in-vivo Pharmacokinetic Assessment - Tawfik MA (Dove Medical Press, 2020)
Mai Ahmed Tawfik, Mina Ibrahim Tadros, Magdy Ibrahim Mohamed, Sara Nageeb El-Helaly Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, EgyptCorrespondence: Mina Ibrahim TadrosCairo University, Kasr El-Aini Street, Cairo 11562, EgyptTel +20 1223620458Fax +20 223628426Email mina.tadros@pharma.cu.edu.egAim: Agomelatine (AGM) is the first melatonergic antidepressant. It suffers from low oral bioavailability (< 5%) due to extensive hepatic metabolism. The current work aimed to develop an alternative AGM-loaded invasomes to enhance transdermal drug bioavailability.Methodology: AGM-loaded invasomes were developed using two drug: lipid ratios (1:10 or 1:7.5), four terpene types (limonene, cineole, fenchone or citral) and two terpene concentrations (0.75% or 1.5%, w/v). They were characterized for drug entrapment efficiency (EE%), particle size (PS), zeta potential (ZP) and drug released percentages after 0.5h (Q0.5h) and 8h (Q8h). The optimum invasomes (I1, I2 and I4) were evaluated for morphology, drug-crystallinity, and ex-vivo drug flux. The variables influencing sonophoresis of the best achieved invasomal gel system (I2) were optimized including, ultrasound frequency (low, LFU or high, HFU), mode (pulsed or continuous), application period (10 min or 15 min) and duty cycle (50% or 100%). AGM pharmacokinetics were evaluated in rabbits following transdermal application of I2-LFU-C4 system, relative to AGM oral dispersion.Results: The superiority of I2 invasomes [comprising AGM and phosphatidylcholine (1:10) and limonene (1.5% w/v)] was statistically revealed with respect to EE% (78.6%), PS (313 nm), ZP (− 64 mV), Q0.5h (30.1%), Q8h (92%), flux (10.79 μg/cm2/h) and enhancement ratio (4.83). The optimum sonophoresis conditions involved application of LFU in the continuous mode for 15 min at a 100% duty cycle (I2-LFU-C4 system). The latter system showed significantly higher Cmax, and relative bioavailability (≈ 7.25 folds) and a similar Tmax (0.5 h).Conclusion: I2-LFU-C4 is a promising transdermal system for AGM.Keywords: agomelatine, invasomes, transdermal, sonophoresis, low frequency ultrasound